2021
DOI: 10.5539/jms.v11n1p218
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Circular Economy and Environmental Certifications: Perceptions of Tourism SMEs

Abstract: Tourism is one of the most important industries in the world. On the one hand, tourism activities provide a significant boost to many national economies but on the other hand, they severely impact the environment. Tourism SMEs are therefore needed to transform their activities from a linear economy to a circular economy (CE). However, the tourism industry has not yet shown a clear and decisive transition towards CE. There is no or very little academic discussion on why the tourism industry has not yet adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…ACAP but also dynamic capabilities and organisational behaviour (Bertassini et al, 2021) can be useful strategy to boost the transition journey. Integrating circular business models and adopting CE initiatives at firm level and along the supply chain (Ethirajan et al, 2020) is pivotal to pursue a new era of business strategies for environmental sustainability (Rehman Khan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ACAP but also dynamic capabilities and organisational behaviour (Bertassini et al, 2021) can be useful strategy to boost the transition journey. Integrating circular business models and adopting CE initiatives at firm level and along the supply chain (Ethirajan et al, 2020) is pivotal to pursue a new era of business strategies for environmental sustainability (Rehman Khan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Using a multiple‐case study approach, in a previous work (Daddi et al, 2019), we focused on an Italian sample of three manufacturing sectors investigating paradoxical tensions and corporate sustainability. However, most research is based on large‐scale surveys (Khan et al, 2021) or single case (Marrucci et al, 2017). Considering that the theory is not easily grasped through quantitative measures and that focusing on a single case may be not representative, Stake (2005) suggested that a multiple‐case study is the best way to frame our study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hotel operators interpret CE as a resource and waste management toolbox to prevent these risks (Sorin & Sivarajah, 2021). In addition, the adoption of environmental certifications or other tools such as carbon footprint would allow tourism SMEs to foster CE (Khan et al, 2021). Although the CE research in tourism has focused on circular practices, the lack of deeper understanding of how companies can apply these in practice is criticised (del Vecchio et al, 2022;Pattanaro & Gente, 2017;Vargas-Sanchez, 2021).…”
Section: Company-level Approachmentioning
confidence: 99%